High density planting of potato (Solanum tuberosum) minitubers for increased seed productivity - KAUR, RATNA PREETI; MINHAS, JOGINDER SINGH; SINGH, SUKHWINDER; SINGH, AKHILESH KUMAR; SINGH, RAJESH KUMAR (The Indian Journal of Agricultural Sciences, 2019)
The experiment was designed to evaluate flatbed planting and density of early potato (Solanum tuberosum L.) seed generation of small minitubers produced under net house conditions of North-western plains. Two varieties Kufri Chandramukhi and Kufri Surya were used in the experiments conducted in 2015–17. The flatbed planting at different plant densities (30×10, 20×10, 15×10 and 10×10 cm) was compared with prevalent ridge and furrow method having 30×10 cm row to row spacing as control in net house.Growth characters (plant height, number of leaves) along with yield parameters (yield, total number of tubers, undersize and seed size tubers) were evaluated for the treatments on per meter square basis. The spacing of 10×10 cm on flat bed significantly outperformed the other treatments in yield as well as total number of tubers. On an average the flat bed planting at 10×10 cm provided a benefit of twice the number of tubers and 1.4 times the yield over control ridge and furrow planting, yielding 259.74 tubers and 5.69 kg on per square metre area basis.The economics of this method was compared to the standard ridge and furrow method, where 1.7 times higher net profit was estimated. The adoption of flat bed planting in net house has tremendous potential in doubling the overall seed production and profitability, which would be itself favourable in advanced seed production generations.